Facilitator empowerment as a catalyst for entrepreneurial character and economic self-reliance of zakat beneficiaries: Evidence from BAZNAS Republik Indonesia - Husnul Khatimah; Qurroh Ayuniyyah; Popy Novita Pasaribu; Immas Nurhayati (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
Productive zakat programs in Indonesia continue to encounter structural challenges in achieving sustainable mustahik empowerment, as many initiatives remain focused on short-term capital distribution rather than long-term capacity building. This study aims to examine how facilitator empowerment and catalytic roles influence mustahik empowerment by positioning entrepreneurial character as a mediating variable. A quantitative explanatory design was employed using survey data collected from mustahik participating in productive zakat programs, which were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess both direct and indirect relationships among constructs. The findings indicate that facilitator empowerment and catalytic roles significantly enhance the entrepreneurial character of mustahik; however, their direct effects on empowerment outcomes are not statistically significant. Instead, entrepreneurial character emerges as the dominant factor and fully mediates the relationship between facilitation processes and empowerment outcomes. These results highlight that sustainable empowerment is primarily driven by internal transformation reflected in entrepreneurial attitudes and behaviors. In conclusion, zakat-based empowerment strategies should shift from output-oriented approaches toward strengthening entrepreneurial character through structured mentoring and catalytic facilitation, thereby promoting long-term economic self-reliance among mustahik.